The use of sprint tests for assessment of speed qualities of elite Australian rules footballers - Young, W.; Russell, A.; Burge, P.; Clarke, A.; Stewart, G. (International Journal of Sports Physiology and Performance, 2008)
The purpose of this study was to determine the relationships between split times within sprint tests over 30 m and 40 m in elite Australian Rules footballers. Methods: Data were analyzed from two Australian Football League (AFL) clubs. The first club (n = 35) conducted a 40-m sprint test and recorded split times at 10 m and 20 m. The second club (n = 30) conducted a 30-m sprint test and recorded splits at 10 m and 20 m. Analyses included calculation of Pearson correlations and common variances between all the split times as well as "flying" times (20-40 m for the first club and 20 to 30 m for the second club). Results: There was a high correlation (r = 0.94) between 10-m time and 20-m time within each club, indicating these measures assessed very similar speed qualities. The correlations between 10-m time and times to 30 m and 40 m decreased, but still produced common variances of 79% and 66% respectively. However when the "flying" times (20-40 m and 20-30 m) were correlated to 10-m time, the common variances decreased substantially to 25% and 42% respectively, indicating uniqueness. Conclusions: It was concluded that 10-m time is a good reflection of acceleration capabilities and either 20 to 40 m in a 40-m sprint test or 20 to 30 m in a 30-m sprint test can be used to estimate maximum speed capabilities. It was suggested that sprint tests over 30 m or 40 m can be conducted indoors to provide useful information about independent speed qualities in athletes.